Laser Therapy for Genitourinary Syndrome of Menopause (GSM): A Stratified Meta-Analysis of Histological, Clinical, and Safety Outcomes - Vani Ardiani; Sri Wahyu Maryuni; Edy Fakhrizal; Dafnil Akhir Putra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Genitourinary syndrome of menopause (GSM) is a prevalent and chronic condition that diminishes quality of life. Vaginal laser therapy is a non-hormonal treatment, but its efficacy and safety require rigorous synthesis. This study was conducted to systematically evaluate the efficacy of laser therapy for GSM by prioritizing high-quality evidence and separately analyzing findings from different study designs, while also providing the first meta-analytic overview of safety. Methods: A systematic search of PubMed, Scopus, Embase, and the Cochrane Library was performed for studies published between January 2015 and December 2024. The primary analysis of efficacy was restricted to randomized controlled trials (RCTs). A separate, secondary analysis was performed on prospective cohort studies. Primary outcomes were changes in vaginal epithelial thickness and the Visual Analog Scale (VAS) for dryness. Secondary outcomes included VAS for dyspareunia, vaginal health index (VHI), female sexual function index (FSFI), and systematically extracted adverse events. Data were pooled using a random-effects model. Results: Seven studies (2 RCTs, 5 cohort studies) involving 595 patients were included. In the primary analysis of RCTs, laser therapy resulted in a significant increase in epithelial thickness (Mean Difference [MD] 50.15 µm) and a significant reduction in VAS for dryness (MD -4.54) with low-to-moderate heterogeneity. The secondary analysis of cohort studies also showed significant improvements, but with extremely high and significant heterogeneity (I² > 80%). Across all studies, reported adverse events were consistently mild and transient, including temporary erythema, edema, and minor discharge. No serious adverse events were reported. Conclusion: Based on high-quality evidence from RCTs, vaginal laser therapy produces statistically significant improvements in the histological and clinical parameters of GSM. Evidence from cohort studies supports this finding but demonstrates considerable variability in real-world settings. While short-term safety appears favorable, the inconsistent treatment effect and lack of long-term data necessitate a cautious approach to patient selection and counseling.